(untitled) (Journal of the Spanish Institute for Strategic Studies, 2018)
The aim of this paper is to elucidate how Resolution 1325 of the Council of the United Nations on Women, Peace and Security has created the need to apply the gender perspective into national legislation; more particularly, into the Draft of Organic Law for the Armed Forces Disciplinary Rules. The influence of gender perspective in the search for a more successful approach to equality between men and women within the process of modernization and improvement of the Armed Forces, where hierarchy and discipline are the founding stones, has been remarkable. Consequently, legislator has been led to foresee not only new disciplinary types, adjusted to a more modern social reality where core personal legal principles must prevail, but also exceptional situations closely associated to that figure.